MODELO DE SUSTENTABILIDADE APLICADO À ANÁLISE DE DESEMPENHO DO PROGRAMA PRODUTOR DE ÁGUA DA AGÊNCIA NACIONAL DE ÁGUAS E SANEAMENTO BÁSICO (ANA) - Silva, Sandriane Kuster Nardi da (2020)
Environmental Service Programs (SAs) have been implemented worldwide, in different areas: conservation of biodiversity, carbon sequestration and storage, scenic beauty and water quality and quantity. Brazil presents recent approaches on incentives to Wate